Preparation method of novel functional diaphragm of lithium ion battery
By preparing Tp-BD-COF/Celgard separators with ordered nanopores and subjecting electrochemical prelithiation, the problems of low ion conductivity and small number of lithium ion migration of the separator of lithium ion are solved, which significantly improves the lithium ion battery capacity and cycle performance.
Patent Information
- Application Number
- CN202411309820.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low ion conductivity and small number of lithium ion migration of existing lithium ion cells limit the performance and application of the battery.
A new functional diaphragm preparation method was adopted to prepare 2,4,6-trihydroxybenzene-1,3,5-triformaldehyde, Tp-BD-COF materials and Tp-BD-COF/Celgard diaphragm and carry out Electrochemical prelithiation treatment forms a separator rich in sequence nanopores to improve the transmission efficiency and electrochemical performance of lithium ions.
The capacity and cycling performance of lithium-ion batteries are significantly improved, the generation of lithium dendrites is inhibited, the polarization caused by different ion gradients is reduced, the interface stability is improved, and the charging and discharging performance of lithium-ion batteries is significantly improved.
Smart Images

Figure CN119181927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a novel functionalized diaphragm for lithium ion batteries. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, fast charge and discharge, and no memory effect. They are widely used in electronic equipment, aerospace, electric vehicles and other fields. Battery separators are known as the third electrode and play a very important role in lithium-ion batteries: 1. Separate the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other and causing internal short circuits; 2. Allow lithium ions to pass through, but the separator does not participate in the battery reaction. The performance of the separator determines the interface structure and internal resistance of the battery, which in turn affects the battery's charge and discharge capacity, cycle performance, rate performance and safety performance.
[0003] At present, commercial lithium-ion battery separators are mainly polyethylene (PE) films, polypropylene (PP) films and PE / PP composite films. Although these separators have high mechanical properties and thermal melt isolation, they have some defects, such as poor wetting properties of electrolytes, low porosity and poor thermal stability, which in turn limit their application in lithium-ion batteries.
[0004] Covalent organic frameworks (COFs) are an emerging type of crystalline porous polymer material composed of organic molecules connected by covalent bonds. They have the characteristics of regular nanochannels and structures that can be clearly designed, providing potential for constructing lithium-ion battery separator modification materials.
[0005] In view of the problems of low ion conductivity and small lithium ion migration number of commercial lithium ion battery diaphragms in the prior art, the present invention provides a method for preparing a novel functionalized diaphragm for lithium ion batteries. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art and solve the problems of low ion conductivity and small lithium ion migration number of commercial lithium ion battery diaphragms in the prior art, the present invention provides a method for preparing a novel functionalized diaphragm for lithium ion batteries.
[0007] The present invention provides a method for preparing a novel functionalized separator for a lithium ion battery, comprising the following steps:
[0008] S1: Preparation of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde;
[0009] S2: Preparation of Tp-BD-COF material by 2,4,6-trihydroxybenzene-1,3,5-tricarboxaldehyde;
[0010] S3: Preparation of Tp-BD-COF / Celgard membrane by Tp-BD-COFF material;
[0011] S4: Application of Tp-BD-COF / Celgard separator in lithium-ion battery assembly;
[0012] S5: The Tp-BD-COF / Celgard separator is subjected to electrochemical pre-lithiation treatment to obtain a new functional separator for lithium-ion batteries.
[0013] As a further improvement of the above scheme, in S1, the preparation method of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde is as follows:
[0014] Weigh hexamethylenetetramine and phloroglucinol and add them into a container; add trifluoroacetic acid under N2 protection, heat and stir the solution at 100°C for 2.5-3h, add hydrochloric acid solution after heating and stirring, heat and stir the solution again at 100°C for about 1-1.5h until the color of the reaction system changes from dark red to orange, and naturally cool to room temperature after the reaction is complete, filter the cooled solution, retain the lower filtrate, extract with dichloromethane, dry and filter with anhydrous magnesium sulfate, and spin-dry the obtained solution through a rotary evaporator to obtain an off-white powder, and obtain a pure 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde sample by sublimation.
[0015] As a further improvement of the above scheme, in S2, the preparation method of the Tp-BD-COF material is as follows:
[0016] Weigh 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde A mmol and p-diaminobenzene B mmol and add them to an ampoule tube, add anisole C mL, ultrasonicate the mixed solution to make the reaction solution system uniform, add acetic acid solution D mL, quickly freeze with liquid nitrogen at 77K, perform three freeze-thaw cycles for degassing, seal the ampoule with a spray gun, wait for the ampoule to return to room temperature, put it in an oven at 100-120°C for reaction for 3-5 days, filter the product, wash it with tetrahydrofuran, use anhydrous tetrahydrofuran as solvent, and repeatedly reflux extract with a Soxhlet extractor for 24 hours to obtain Tp-BD-COF material;
[0017] Among them, A:B:C:D=0.05~0.2:0.075~0.3:1.5~2:0.2~0.5.
[0018] As a further improvement of the above scheme, in S3, the preparation method of Tp-BD-COF / Celgard membrane is as follows:
[0019] The Tp-BD-COF material was dried, and Kmg of the dried Tp-BD-COF and Lmg of polyvinylidene fluoride were weighed and ground into a 100-mesh powder in a mortar. Then, the powder was put into a container, and M mL of N-methylpyrrolidone was added. The mixture was stirred for 6 to 12 hours. The slurry after stirring was evenly coated on the Celgard diaphragm. The diaphragm coated with the slurry was placed in a vacuum drying oven and dried at 40 to 70°C for 20 to 24 hours to obtain a Tp-BD-COF / Celgard diaphragm.
[0020] Among them, K:L:M=80~90:10~20:1~1.5.
[0021] As a further improvement of the above scheme, in S4, the steps of assembling the lithium-ion battery are as follows:
[0022] The active material, PVDF and acetylene black were mixed in a mass ratio of 7-9:0.5-2:0.5-2, N-methylpyrrolidone was added, and the mixture was ground into a slurry with a certain fluidity. The slurry was evenly coated on aluminum foil and dried overnight at 120-140°C. The battery size was selected, and the aluminum foil was cut into discs of corresponding size. The active material loading was controlled to be 1.5-2 mg / cm 2 The prepared Tp-BD-COF / Celgard separator and electrode are assembled in a button cell to obtain a lithium-ion battery.
[0023] As a further improvement of the above scheme, the electrochemical pre-lithiation treatment includes: a lithium-ion battery with a Tp-BD-COF / Celgard separator is composed of a lithium sheet, an electrolyte and a Tp-BD-COF / Celgard separator, and lithium ions are diffused through the electrolyte to the Tp-BD-COF / Celgard separator by applying different voltages, scanning speeds, and scanning circles to complete the pre-lithiation process.
[0024] As a further improvement of the above solution, the active material is LiFePO4 powder or NCM811 powder.
[0025] The invention discloses an application of a new functionalized separator for lithium-ion batteries.
[0026] The beneficial effects achieved by the present invention are as follows: compared with the prior art, the Tp-BD-COF / Celgard membrane in the preparation method of a novel functionalized membrane for lithium-ion batteries provided by the present invention is a carbonyl-rich covalent organic framework membrane, which has ordered nanoscale pores, which can effectively block the shuttling of anions, hinder the transmission of lithium salt anions, and uniformly transmit lithium ions, thereby increasing the number of lithium ion migrations, effectively inhibiting the formation of lithium dendrites, achieving good electrochemical performance, and reducing the polarization caused by different ion gradients, thereby improving interface stability. In addition, the Tp-BD-COF / Celgard membrane that has been electrochemically pre-lithiated improves the capacity and first effect of the lithium-ion battery. Compared with commercial membranes, the modified membrane prepared by the present invention has excellent proton conductivity and can significantly improve the capacity and cycle performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a synthetic route diagram of Tp-BD-COF in the present invention;
[0028] Figure 2 is the X-ray powder diffraction pattern of Tp-BD-COF in the present invention;
[0029] Figure 3 is the Fourier transform infrared spectrum of Tp-BD-COF in the present invention;
[0030] Figure 4 is the Nyquist plot of the Tp-BD-COF / Celgard membrane of the present invention;
[0031] Figure 5 This is the Nyquist plot of a commercial diaphragm;
[0032] Figure 6 This is a test diagram of the cycle performance of the LiFePO4 battery in an embodiment of the present invention;
[0033] Figure 7 This is a test diagram of the cycle performance of the LiFePO4 battery after pre-lithiation in the present invention;
[0034] Figure 8 This is a test diagram of the cycle performance of the NCM811 battery in the present invention;
[0035] Fig. 9 This is a test diagram of the cycle performance of the NCM811 battery after pre-lithiation in the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0037] like Figures 1 to 9As shown, the present method provides a method for preparing a novel functionalized separator for lithium-ion batteries, comprising the following steps:
[0038] S1: Preparation of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde;
[0039] Specifically, the preparation method of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde is as follows: weigh hexamethylenetetramine and phloroglucinol and add them to a container; add trifluoroacetic acid under N2 protection, heat and stir the solution at 100°C for 2.5 to 3 hours, add 140 to 160 mL of hydrochloric acid solution after heating and stirring, heat and stir the solution again at 100°C for about 1 to 1.5 hours, and the color of the reaction system changes from dark red to orange. After the reaction is complete, it is naturally cooled to room temperature, and the cooled solution is filtered, and the lower filtrate is retained, extracted with 350-500 mL of dichloromethane, dried and filtered with anhydrous magnesium sulfate, and the obtained solution is spin-dried by a rotary evaporator to obtain an off-white powder, and a pure 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde sample is obtained by sublimation.
[0040] S2: Preparation of functionalized covalent organic framework Tp-BD-COF material by 2,4,6-trihydroxybenzene-1,3,5-tricarboxaldehyde;
[0041] Specifically, the preparation method of Tp-BD-COF material is as follows: weigh 2,4,6-trihydroxybenzene-1,3,5-triformaldehyde Ammol and p-diaminobenzene Bmmol and add them to an ampoule tube, add anisole CmL, ultrasonicate the mixed solution to make the reaction solution system uniform, add acetic acid solution DmL, quickly freeze with liquid nitrogen at 77K, perform three freeze-thaw cycles for degassing, seal the ampoule with a spray gun, wait for the ampoule to return to room temperature, put it in an oven at 100-120°C for reaction for 3-5 days, filter the product, wash it with tetrahydrofuran, use anhydrous tetrahydrofuran as solvent, and repeatedly reflux extract with a Soxhlet extractor for 24h to obtain Tp-BD-COF material;
[0042] Among them, A:B:C:D=0.05~0.2:0.075~0.3:1.5~2:0.2~0.5,
[0043] S3: Preparation of Tp-BD-COF / Celgard membrane using Tp-BD-COF material;
[0044] Specifically, the preparation method of Tp-BD-COF / Celgard membrane is as follows: drying the Tp-BD-COF material, weighing the dried Tp-BD-COF K mg and the binder polyvinylidene fluoride L mg, putting them into a mortar and grinding them into a 100-mesh powder, then putting them into a container, adding N-methylpyrrolidone M mL, stirring for 6 to 12 hours, and evenly coating the stirred and mixed slurry on the Celgard membrane, placing the membrane coated with the slurry in a vacuum drying oven, and drying at 40 to 70° C. for 20 to 24 hours to obtain a Tp-BD-COF / Celgard membrane;
[0045] Among them, K:L:M=80~90:10~20:1~1.5.
[0046] S4: Application of Tp-BD-COF / Celgard separator in lithium-ion battery assembly;
[0047] Specifically, the assembly steps of the lithium-ion battery are as follows: the active material, PVDF, and acetylene black are mixed in a mass ratio of 7-9:0.5-2:0.5-2, N-methylpyrrolidone is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on an aluminum foil and dried overnight at 120-140°C for 12-24 hours. The battery size is selected, and the aluminum foil is cut into discs of corresponding size, and the active material loading is controlled to be 1.5-2 mg / cm 2 The prepared Tp-BD-COF / Celgard separator and electrode are assembled in a button cell to obtain a lithium-ion battery.
[0048] The active material is any one of positive electrode materials such as LiFePO4 powder, NCM811 powder, Li4Ti5O12 powder, LiCoO2 powder, etc.
[0049] S5: Physical pre-lithiation treatment is performed on the Tp-BD-COF / Celgard separator to obtain a new functional separator for lithium-ion batteries.
[0050] Specifically, the electrochemical pre-lithiation treatment includes: a lithium-ion battery with a Tp-BD-COF / Celgard separator is assembled into a battery by combining lithium sheets, an electrolyte and a Tp-BD-COF / Celgard separator, and lithium ions are diffused through the electrolyte to the Tp-BD-COF / Celgard separator by applying different voltages, scanning speeds and scanning circles to complete the pre-lithiation process and obtain a new functional separator for lithium-ion batteries.
[0051] The invention discloses an application of a new functionalized separator for lithium-ion batteries.
[0052] Example 1 Preparation of covalent organic framework
[0053] The following steps are involved:
[0054] S1: Preparation of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde;
[0055] Hexamethylenetetramine (15.098 g, 108 mmol) and phloroglucinol (6.014 g, 49 mmol) were weighed and added to a 500 mL two-necked flask; 90 mL of trifluoroacetic acid was added under N2 protection, the solution was heated and stirred at 100 ° C for 2.5 to 3 h, and then 150 mL of hydrochloric acid solution with a solution concentration of 3 mol / L was added. The solution was heated and stirred again at 100 ° C for about 1.5 h, and the color of the reaction system changed from dark red to orange. After the reaction was completed, it was naturally cooled to room temperature, and the color of the reaction system changed from dark red to orange. The cooled solution was filtered, and the lower filtrate was retained. 350 mL of dichloromethane was used for extraction, and the solution was dried and filtered with anhydrous magnesium sulfate. The obtained solution was spin-dried by a rotary evaporator to obtain an off-white powder, and a pure 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde sample was obtained by sublimation.
[0056] S2: Preparation of Tp-BD-COF material by 2,4,6-trihydroxybenzene-1,3,5-tricarboxaldehyde;
[0057] The prepared weighed 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde A mmol and p-diaminobenzene Bmmol were added to an ampoule tube, and the reaction solvent anisole C mL was added. The mixed solution was ultrasonicated for 5 minutes to make the reaction solution system uniform, and 12 mol / L acetic acid solution D mL was added. The mixture was rapidly frozen with liquid nitrogen at 77K, and three freeze-thaw cycles were performed for degassing. The ampoule was sealed with a spray gun, and the ampoule was returned to room temperature and placed in an oven at 120°C for reaction for 96 hours. The hot reaction bottle was opened, the product was filtered, and washed with tetrahydrofuran. Anhydrous tetrahydrofuran was used as a solvent and the Soxhlet extractor was repeatedly refluxed for 24 hours to obtain Tp-BD-COF material;
[0058] Preferably, in this embodiment, A:B:C:D=0.1:0.15:2:0.5.
[0059] Characterization of Tp-BD-COF:
[0060] Figure 2This is the X-ray powder diffraction pattern (PXRD) of Tp-BD-COF, which shows that the synthesized Tp-BD-COF material has good crystallinity, and the crystallinity is 2θ=3.5°, 6.0°, 11.2°, 13.4°, and 26.1°, respectively. The strongest peak 2θ=3.5° corresponds to the (100) plane of Tp-BD-COF, and 2θ=26.1° corresponds to the (001) plane of Tp-BD-COF, which is consistent with the simulated Tp-BD-COF.
[0061] Figure 3 This is the Fourier transform infrared spectrum (FT-IR) of Tp-BD-COF. It can be clearly observed that -C=O (1649cm -1 ) and the NH stretching (3400-3200cm-1) of free -NH2 in p-diaminobenzidine. The above peaks were not observed in the synthesized Tp-BD-COF, indicating that the reaction should be complete. The successful synthesis of Tp-BD-COF material was shown by PXRD and FT-IR.
[0062] S3: Preparation of Tp-BD-COF / Celgard membrane by Tp-BD-COFF material;
[0063] The Tp-BD-COF material was dried, and Kmg of the dried Tp-BD-COF and Lmg of polyvinylidene fluoride were weighed and ground into a 100-mesh powder in a mortar. Then, the powder was put into a glass bottle, and M mL of N-methylpyrrolidone was added. The mixture was stirred at room temperature for 8 h. The stirred and mixed slurry was evenly coated on the Celgard diaphragm using an automatic coating machine. The diaphragm coated with the slurry was placed in a vacuum drying oven and dried at 60°C for 24 h to obtain a Tp-BD-COF / Celgard diaphragm.
[0064] Preferably, in this embodiment, K:L:M=80:20:1.
[0065] Conductivity test of Tp-BD-COF / Celgard membrane:
[0066] Figure 4 This is the Nyquist plot of Tp-BD-COF / Celgard membrane. The ionic conductivity at room temperature is 2.48×10 - 4 S / cm.
[0067] Figure 5 This is the Nyquist plot of a commercial separator. The lithium ion conductivity at room temperature is 5.18×10 -5 S / cm.
[0068] Example 2 Application of new functionalized separator for lithium-ion batteries in separators for lithium-ion batteries
[0069] Application in LiFePO4 battery:
[0070] S1: Tp-BD-COF / Celgard separator was used for the assembly of lithium-ion batteries;
[0071] Specifically, the assembly steps of the lithium-ion battery are as follows: LiFePO4 is selected as the active material, LiFePO4 powder, PVDF, and acetylene black are mixed in a mass ratio of 8:1:1, N-methylpyrrolidone is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on an aluminum foil and dried at 120°C for 12 hours, and then cut into small discs (diameter: 12 mm), and the LiFePO4 loading is controlled to be 1.5-2 mg / cm 2 The prepared Tp-BD-COF / Celgard membrane, LiFePO4 cathode and lithium metal anode were installed in a CR2016 button cell in an argon glove box environment with O2 and H2O less than 0.1 ppm to obtain a lithium-ion battery. The liquid electrolyte was 1 M LiPF6 in EC / DMC / DEC (1 / 1 / 1, v / v / v).
[0072] The assembled lithium-ion battery is charged and discharged using the Xinwei system:
[0073] Figure 5 This is a test chart of the cycle performance of a lithium-ion battery. The test temperature is 28-30°C, and the lithium-ion battery is cycled 100 times between 2.5-4.2V at a rate of 0.3C (1C=180mAh / g).
[0074] After 100 cycles, the capacity of the battery using the Tp-BD-COF / Celgard separator remained constant at around 155 mAh / g, maintaining a high capacity retention rate of 99%.
[0075] S2: Electrochemical pre-lithiation treatment of Tp-BD-COF / Celgard separator.
[0076] Specifically, the electrochemical pre-lithiation treatment includes: a lithium-ion battery with a Tp-BD-COF functionalized covalent organic framework material / Celgard separator is assembled into a battery by combining a lithium sheet, an electrolyte and a Tp-BD-COF / Celgard separator, and lithium ions are diffused through the electrolyte to the Tp-BD-COF / Celgard separator by applying different voltages, scanning speeds and scanning circles to complete the pre-lithiation process.
[0077] Preferably, the best conditions are a voltage range of 2.5-4.2 V, a scan rate of 1 mV / s, and a scan number of 6 circles for electrochemical pre-lithiation treatment.
[0078] Electrochemical testing of lithium-ion batteries with pre-lithiated separators:
[0079] The pre-lithiation lithium-ion battery is subjected to charge and discharge tests. Figure 6 This is a cycle performance test chart of a button cell after pre-lithiation. The test temperature is 28-30°C, and the lithium-ion battery is cycled 100 times at 2.5-4.2V at a rate of 0.3C (1C = 180mAh / g). After 100 cycles, the capacity of the pre-lithiation battery is constant at around 160mAh / g, maintaining a high capacity retention rate of 98%.
[0080] Example 3 Application of new functionalized separator for lithium-ion batteries in separators for lithium-ion batteries
[0081] Application in NCM811 battery:
[0082] S4: Application of Tp-BD-COF / Celgard separator in lithium-ion battery assembly;
[0083] Specifically, the assembly steps of the lithium-ion battery are as follows: NCM811 is selected as the active material, NCM811 powder, PVDF, and acetylene black are mixed in a mass ratio of 8:1:1, N-methylpyrrolidone is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on an aluminum foil and dried at 120°C for 12 hours, and then cut into small discs (diameter: 12 mm), and the NCM811 loading is controlled to be 1.5-2 mg / cm2. The prepared Tp-BD-COF / Celgard membrane, NCM811 cathode, and lithium metal anode are placed in an argon glove box environment with O2 and H2O less than 0.1 ppm. A lithium-ion battery is obtained, and the liquid electrolyte is 1M LiPF6 EC / DMC / DEC (1 / 1 / 1, v / v / v).
[0084] The assembled lithium-ion battery is charged and discharged using the Xinwei system:
[0085] Figure 5 This is a test chart of the cycle performance of lithium-ion batteries. The test temperature is 28-30°C, and the lithium-ion battery is cycled 100 times at a rate of 0.3C (1C = 180mAh / g) between 3-4.35V. After 100 cycles, the capacity of the battery using the Tp-BD-COF / Celgard separator is constant at around 128mAh / g, maintaining a high capacity retention rate of 99%.
[0086] S5: Electrochemical pre-lithiation treatment of Tp-BD-COF / Celgard separator.
[0087] Specifically, the electrochemical pre-lithiation treatment includes: a lithium-ion battery with a Tp-BD-COF / Celgard separator is assembled into a battery by combining lithium sheets, an electrolyte and a Tp-BD-COF / Celgard separator, and lithium ions are diffused through the electrolyte to the Tp-BD-COF / Celgard separator by applying different voltages, scanning speeds and scanning circles to complete the pre-lithiation process.
[0088] Preferably, the best conditions are that the voltage range is 3-4.35 V, the scanning speed is 0.1 mV / s, and the number of scanning circles is 4 for electrochemical pre-lithiation treatment.
[0089] Electrochemical testing of lithium-ion batteries with pre-lithiated separators:
[0090] The pre-lithiation lithium-ion battery is subjected to charge and discharge tests. Figure 6 This is a cycle performance test chart of a button cell after pre-lithiation. The test temperature is 28-30°C, and the lithium-ion battery is cycled 100 times at a rate of 0.3C (1C = 180mAh / g) between 3-4.35V. After 100 cycles, the capacity of the pre-lithiation battery is constant at around 135mAh / g, maintaining a high capacity retention rate of 99%.
[0091] The above describes in detail the implementation modes of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes. The implementation modes can still be changed within the knowledge scope of ordinary technicians in the field. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a novel functionalized diaphragm for a lithium-ion battery, characterized in that: The following steps are involved: S1: Preparation of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde; S2: Preparation of Tp-BD-COF material by 2,4,6-trihydroxybenzene-1,3,5-tricarboxaldehyde; S3: Preparation of Tp-BD-COF / Celgard membrane using Tp-BD-COF material; S4: Tp-BD-COF / Celgard separator was used for the assembly of lithium-ion batteries; S5: Electrochemical pre-lithiation treatment of Tp-BD-COF / Celgard separator.
2. The method for preparing a novel functionalized diaphragm for lithium-ion batteries according to claim 1, characterized in that: In S1, the preparation method of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde is as follows: Weigh hexamethylenetetramine and phloroglucinol and add them into a container; add trifluoroacetic acid under N2 protection, heat and stir the solution at 100°C for 2.5-3h, add hydrochloric acid solution after heating and stirring, heat and stir the solution again at 100°C for about 1-1.5h until the color of the reaction system changes from dark red to orange, and naturally cool to room temperature after the reaction is complete, filter the cooled solution, retain the lower filtrate, extract with dichloromethane, dry and filter with anhydrous magnesium sulfate, and spin-dry the obtained solution through a rotary evaporator to obtain an off-white powder, and obtain a pure 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde sample by sublimation.
3. The method for preparing a novel functionalized diaphragm for lithium ion batteries according to claim 1, characterized in that: In S2, the preparation method of Tp-BD-COF material is as follows: Weigh 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde A mmol and p-diaminobenzene B mmol and add them to an ampoule tube, add anisole C mL, ultrasonicate the mixed solution to make the reaction solution system uniform, add acetic acid solution D mL, quickly freeze with liquid nitrogen at 77K, perform three freeze-thaw cycles for degassing, seal the ampoule with a spray gun, wait for the ampoule to return to room temperature, put it in an oven at 100-120°C for reaction for 3-5 days, filter the product, wash it with tetrahydrofuran, use anhydrous tetrahydrofuran as solvent, and repeatedly reflux extract with a Soxhlet extractor for 24 hours to obtain Tp-BD-COF material; Among them, A:B:C:D=0.05~0.2:0.075~0.3:1.5~2:0.2~0.
5.
4. The method for preparing a novel functionalized diaphragm for lithium-ion batteries according to claim 1, characterized in that: In S3, the Tp-BD-COF / Celgard membrane preparation method is as follows: The Tp-BD-COF material was dried, and Kmg of the dried Tp-BD-COF and Lmg of polyvinylidene fluoride were weighed and ground into a 100-mesh powder in a mortar. Then, the powder was put into a container, and M mL of N-methylpyrrolidone was added. The mixture was stirred for 6 to 12 hours. The slurry after stirring was evenly coated on the Celgard diaphragm. The diaphragm coated with the slurry was placed in a vacuum drying oven and dried at 40 to 70°C for 20 to 24 hours to obtain a Tp-BD-COF / Celgard diaphragm. Among them, K:L:M=80~90:10~20:1~1.
5.
5. The method for preparing a novel functionalized diaphragm for lithium-ion batteries according to claim 1, characterized in that: In S4, the assembly steps of lithium-ion batteries are as follows: The active material, PVDF and acetylene black were mixed in a mass ratio of 7-9:0.5-2:0.5-2, N-methylpyrrolidone was added, and the mixture was ground into a slurry with a certain fluidity. The slurry was evenly coated on aluminum foil and dried overnight at 120-140°C. The battery size was selected, and the aluminum foil was cut into discs of corresponding size. The active material loading was controlled to be 1.5-2 mg / cm 2 The prepared Tp-BD-COF / Celgard separator and electrode are assembled in a button cell to obtain a lithium-ion battery.
6. The method for preparing a novel functionalized diaphragm for lithium ion batteries according to claim 1, characterized in that: The electrochemical pre-lithiation treatment includes: applying different voltages, scanning speeds, and scanning circles to allow lithium ions to diffuse through the electrolyte to the Tp-BD-COF / Celgard separator to complete the pre-lithiation process.
7. The method for preparing a novel functionalized diaphragm for lithium-ion batteries according to claim 5, characterized in that: The active material is any one of LiFePO4 powder, NCM811 powder, Li4Ti5O12 powder and LiCoO2 powder.
8. Application of the novel functionalized separator for lithium ion batteries as claimed in claim 1 in separators for lithium ion batteries.
Citation Information
Patent Citations
Functional diaphragm as well as preparation method and application thereof
CN114188669A
Covalent organic framework modified high-ion-selectivity permeable membrane as well as preparation method and application thereof
CN118634653A
Cited By
Piezoelectric self-adaptive diaphragm as well as preparation method and application thereof
CN121688350A
Functional diaphragm, preparation method thereof and lithium ion battery
CN122011477A
